An exposure‐response analysis of ponesimod clinical efficacy in a randomized phase III study in patients with relapsing multiple sclerosis - Belén Valenzuela; Per Olsson Gisleskog; Italo Poggesi; Tatiana Sidorenko; Michel Burcklen; Hilke Kracker; Juan Jose Pérez‐Ruixo (Wiley, 2022)
Abstract The efficacy of ponesimod and teriflunomide for the treatment of relapsing multiple sclerosis (MS) was compared in a randomized phase III trial. This study explores the exposure‐response (E‐R) relationships of efficacy end points (annualized relapse rate [ARR] and combined unique active lesions [CUALs]) of ponesimod observed in this trial. The E‐R relationships were described using nonlinear mixed effects models for count data. The effect of baseline covariates (demography and prognostic factors) was also explored. Ponesimod 20 mg reduced ARR (primary end point) by 30.5% (95% confidence interval [CI]: 9.8% to 46.4%) and the number of CUALs by 56% (95% CI: 46% to 64%) between baseline and week 108 compared to teriflunomide 14 mg. The E‐R analyses indicated a significant relationship between ARR and CUAL. In turn, CUAL was significantly related to ponesimod systemic exposure. Based on these relationships, the predicted reduction of ARR was relatively flat in the range of ponesimod systemic exposure achieved with the 20 mg clinical dose: the expected ARR decrease ranged from 28% (95% CI: 11% to 42%) at the 5th percentile of ponesimod exposure to 34% (95% CI: 19% to 47%) at the 95th percentile. No significant baseline covariates affected the ponesimod effects and, consequently, dosage adjustments are not warranted by these analyses. Although significant relationships were found between ARR and CUAL and between ponesimod exposure and CUAL, these analyses were supportive of the use of a flat 20 mg maintenance dose for ponesimod in adult patients with MS.